2008
DOI: 10.1021/jf802382y
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Profiling in Leaves of Citrus Genotypes under Different Environmental Situations

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 37 publications
5
48
0
3
Order By: Relevance
“…The most differentiating compounds were quercetin, kaempferol, eriodictyol and apigenin. Higher relative reduction in flavonoids was observed in the sensitive genotype, which may indicate that the stability of flavonoid content is important in maintaining higher antioxidant activity under water stress (Djoukeng et al 2008). Wu and co-workers showed that it was possible to use isoflavonoids to discriminate between closely related soybean genotypes.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The most differentiating compounds were quercetin, kaempferol, eriodictyol and apigenin. Higher relative reduction in flavonoids was observed in the sensitive genotype, which may indicate that the stability of flavonoid content is important in maintaining higher antioxidant activity under water stress (Djoukeng et al 2008). Wu and co-workers showed that it was possible to use isoflavonoids to discriminate between closely related soybean genotypes.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Among aglycone forms, quercetin, naringenin and hesperitin are the main flavonoids. Whereas, the glycoside forms can be further classified into rutinosides and neohesperidosides (Djoukeng et al, 2008). Neohesperidosides (e.g., naringin, neohesperidin and neoeriocitrin) contain a sugar neohesperidose (rhamnosyl-a-1, 2 glucose) and they are bitter in taste, while rutinosides (rutin, hesperidin and didymin) contain a disaccharide residue e.g., rutinose (ramnosyl-a-1,6 glucose) which makes them tasteless (Macheix et al, 1990).…”
Section: Citrus Flavonoidsmentioning
confidence: 99%
“…The diethyl ether fraction was chromatographed on a Diaion HP-20 column and HPLC to obtain 8, 14, and 15. The known compounds (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were identified based on spectroscopic data as hypolaetin 7-O-b-D-glucopyranoside (6) [18,19], luteolin (7) [20], acacetin (8) [21], hypolaetin (9) [22], luteolin 7-O-[6 00 -O-(trans-caffeoyl)]-b-D-glucopyranoside (10) [20,23] [20], luteolin 7-O-b-D-glucuronopyranoside (12) [24], luteolin 7-O-rutinoside (13) [25,26], 12-O-demethylcryptojaponol (14) [27], 6a-hydroxydemethylcryptojaponol (15) [28], and incanide B (20) [29]. Four phenylethanoid glycosides, acteoside (16), isoacteoside (17), martynoside (18), and stachysoside (19) were identified by comparison with compounds isolated previously from Leucosceptrum japonicum by our group [30] (Fig.…”
Section: Resultsmentioning
confidence: 99%